DETERMINAN NIAT BELI MAKANAN ORGANIK: SIKAP UNTUK MEMBELI SEBAGAI VARIABEL MEDIASI - Shella F. Eles; Sabrina O. Sihombing (Universitas Mercu Buana, 2016)
Abstract. The purpose of this study is to identify whether environmental concern,consumers‟ perceptions, health consciousness, subjective norms, and attitude have apositive relationship towards organic food purchase intention. The type of researchused for this study is descriptive research with non probability sampling design. Thenumber of respondents was 202 respondents. Hypotheses were tested using StructuralEquations Model (SEM). The results showed that there are three unsupportedhypotheses out of five hypotheses. Supported hypotheses are hypothesis 2 andhypothesis 5. The supported hypotheses are consumers‟ perceptions and attitude.Furthermore, this research showed that consumers‟ perceptions and attitude have apositive relationship toward purchase intention.